Mapping Global Research Trends on Digital Transformation, Innovation Capability, and Knowledge Management in Startup Competitive Advantage: A Bibliometric Study - Candra Agus Wahyudhi; Acep Fatchuroji (Jurnal Bisnis dan Manajemen West Science, 2025)
This study maps global research trends on digital transformation, innovation capability, and knowledge management within the context of startup competitive advantage using a bibliometric and science-mapping approach. Data were extracted from the Scopus database and analyzed using VOSviewer through network visualization, overlay mapping, density analysis, author collaboration mapping, and country collaboration networks. The findings reveal three dominant thematic clusters: digital transformation as an ecosystem-driven strategic capability, innovation capability as a core driver of entrepreneurial agility, and knowledge management as the foundation for organizational learning and adaptability. Temporal evolution analysis shows a shift from early digitalization research toward advanced topics such as platform ecosystems, sustainable digital entrepreneurship, and knowledge-intensive services. Overall, the study highlights that startup competitive advantage emerges from the integration of technological readiness, innovation-driven value creation, and dynamic knowledge flows. These findings provide a consolidated understanding of the field and identify promising directions for future research on digital competitiveness and entrepreneurial ecosystems.